2009
DOI: 10.1111/j.1365-3016.2008.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural tube defects: an analysis of neighbourhood‐ and individual‐level socio‐economic characteristics

Abstract: Summary Several studies have reported that neural tube defects (NTD) occur more frequently among children born to women of lower socio-economic status (SES). This study investigated the relationship between individual- and neighbourhood-level SES and the risk of an NTD-affected pregnancy. Data were drawn from a population-based case-control study of fetuses and infants among a cohort of California births between July 1999 and June 2003. Information on individual SES was obtained via telephone interviews with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
2
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 24 publications
1
53
2
5
Order By: Relevance
“…It has been reported that women who live in low-socioeconomic-status neighborhoods and did not graduate from high school have a significantly higher risk of spinal dysraphism during pregnancy than mothers with a high school or higher education who live in the same region [24]. Another study reported a similar association of maternal educational status and spinal dysraphism among Hispanic Americans [25].…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that women who live in low-socioeconomic-status neighborhoods and did not graduate from high school have a significantly higher risk of spinal dysraphism during pregnancy than mothers with a high school or higher education who live in the same region [24]. Another study reported a similar association of maternal educational status and spinal dysraphism among Hispanic Americans [25].…”
Section: Discussionmentioning
confidence: 97%
“…A low level of maternal education 38 and food shortage 39 have been identified as possible risk factors for neural tube defects, in addition to the use of medications which interfere with the metabolism of folic acid (anti-epileptics, aspirin, methotrexate, sulfasalazine etc. ), hyperthermia, use of tobacco and excessive doses of vitamin A (> 15,000IU) during pregnancy 40 .…”
Section: • Environmentmentioning
confidence: 99%
“…2 Different studies have studied familiar and regional adverse social determinants in relation to perinatal outcome, such as neonatal mortality, 3 low birth weight 4 and prematurity, 5 but not in relation to congenital anomalies. Among the few reported causes on this issue, a low maternal socioeconomic level (SEL) has been associated with a higher risk of having a newborn infant with cleft lip, 6,9 neural tube defects, 7 and heart diseases. 8,9 The etiology of poverty in relation to congenital anomalies is varied, indirect and non-specific, and includes environmental conditions (pollution, v i o l e n c e , s t r e s s , e t c . )…”
Section: Introductionmentioning
confidence: 99%